Access to safe drinking water, good sanitation, occurrence of under-five mortality and standard of living in developing countries : system GMM approach - Waziri, Salisu Ibrahim; Norashidah Mohamed Nor; Law, Siong Hook; Azman Hassan (Penerbit Universiti Kebangsaan Malaysia, 2018)
The present study aims to examine the impact of access to safe drinking water and good sanitation on under-five mortality in developing countries by using a panel data-set for 81 selected developing countries with data spanning from 2008 to 2016. System generalized method of moments (GMM) was applied to achieve the objectives of the study. The findings of the first objective reveal that access to safe drinking water is negative and significantly related to under-five mortality. Similarly, the result of the second objective shows that good sanitation is also negatively related with the prevalence of under-five mortality in developing countries. The results have implication on the availability of future workforce and the citizens’ standard of living in developing countries. Thus, the study recommends that, by providing safe drinking water and good sanitation for all, could potentially reduce water-related diseases and death prevalence amongst children below the age of five, especially in developing countries where more than 80% of global under-five mortality exists.